1987
DOI: 10.1021/la00074a012
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni effect and relaxations of surface potential in pentadecanoic acid and octadecanol monolayers

Abstract: The time evolutions of the surface potential have been measured during and after step compressions of pentadecanoic acid and octadecanol monolayers at the air-water interface, by use of the radioactive electrode method. At each compression step, the Marangoni effect is observed. The propagation times obtained experimentally are in good agreement with the theoretical predictions. The phase transitions are associated with relaxations of the surface potential at the breakpoint (the LE breakdown) of the liquid exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Instead, an immobilization of the particles at the watertoluene interface is observed and the sides of the glass vessel are coated with a metallic film. This is very similar to the Marangoni growth mechanism that results in the spreading of liquid films on glass based on the surface tension gradients [50]. Both the as-prepared aqueous-phase particles and the corresponding (MPA + TOABr)-capped particles deposited from toluene after phase transfer are shown.…”
Section: Resultssupporting
confidence: 67%
“…Instead, an immobilization of the particles at the watertoluene interface is observed and the sides of the glass vessel are coated with a metallic film. This is very similar to the Marangoni growth mechanism that results in the spreading of liquid films on glass based on the surface tension gradients [50]. Both the as-prepared aqueous-phase particles and the corresponding (MPA + TOABr)-capped particles deposited from toluene after phase transfer are shown.…”
Section: Resultssupporting
confidence: 67%
“…For example, as early as 1939 Nutting and Harkins 12 observed that the rate of compression had an effect on the form and position of isotherms obtained for monolayers of fatty acids. Recently, Bois et aL [13][14][15] have reported that a monolayer which was continuously compressed until 11" rose Z 1 dyn/cm could often show significant relaxation in 11" when the compression was stopped. As a result, the authors stated that isotherms obtained with continuous compression must be interpreted judiciously because the compression rates generally used are much greater than the relaxation rates of the monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…However, quite frequently, monolayers are unstable at surface pressures much below the collapse pressure. Besides film fracture, other phenomena related to the film instability are the loss of molecules from the surface either by evaporation (13) or by dissolution (14), molecular rearrangement during compression (15), chemical reactions on the interface (16), hydration of polar groups (17), the Marangoni effect (18), surface rheology (19), and adsorption from the bulk solution.…”
mentioning
confidence: 99%